2009
DOI: 10.1007/s10803-009-0772-x
|View full text |Cite
|
Sign up to set email alerts
|

The Children’s Empathy Quotient and Systemizing Quotient: Sex Differences in Typical Development and in Autism Spectrum Conditions

Abstract: Children's versions of the Empathy Quotient (EQ-C) and Systemizing Quotient (SQ-C) were developed and administered to n = 1,256 parents of typically developing children, aged 4-11 years. Both measures showed good test-retest reliability and high internal consistency. As predicted, girls scored significantly higher on the EQ-C, and boys scored significantly higher on the SQ-C. A further sample of n = 265 children with Autism Spectrum Conditions (ASC) scored significantly lower on the EQ-C, and significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
241
5
41

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(323 citation statements)
references
References 70 publications
36
241
5
41
Order By: Relevance
“…Items intending to measure each of the 5 domains of interest (social, communication, imagination, attention to detail, and attention switching) show high alpha coefficients. These findings are consistent with the findings on the English AQ adolescent version ) on the English AQ Child version (Auyeung et al 2007) and on the English EQ-SQ child version (Auyeung et al 2009). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Items intending to measure each of the 5 domains of interest (social, communication, imagination, attention to detail, and attention switching) show high alpha coefficients. These findings are consistent with the findings on the English AQ adolescent version ) on the English AQ Child version (Auyeung et al 2007) and on the English EQ-SQ child version (Auyeung et al 2009). …”
Section: Discussionsupporting
confidence: 91%
“…In the English SQ child study, similar results were found, except that they did find gender differences on the SQ in general. Boys scored significantly higher than girls, consistent with studies demonstrating a male advantage for visuo-spatial ability and a preference for 'systems' (Auyeung et al 2009). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The result repeated itself in other studies conducted with individuals from varying age groups (children, young people, elderly) and it is again seen that females rank higher on empathy scores (Auyeung, Baron-Cohen, Wheelwright, Samarawickrema & Atkinson, 2009;Wheelwright et al 2006). Baron-Cohen et al have developed a empathy-systematize measurement (Child Empathy-Systemizing Quotient EQ-SQ) (Baron-Cohen, Knickmeyer & Belmonte, 2005) with which they can point out the differences in systematizing and empathy abilities between individuals on the autism spectrum and individuals with typical development.…”
Section: Empathizing-systemizing Theorymentioning
confidence: 59%
“…However, higher empathizing scores were associated with earlier puberty in zero-order correlations. Although this comports with the hypothesis that autistic-like traits are associated with a slow LH strategy (Del Giudice et al 2010, the association would not survive correction for multiple statistical testing, performance on the eyes test was unrelated to pubertal timing, and systemizing was related to puberty in the opposite direction: less autistic-like performance (Auyeung et al 2009b) was associated with earlier puberty.…”
Section: Discussionmentioning
confidence: 95%